Effective management and culture : an analysis of three English-Speaking Caribbean countries - Punnett, Betty-Jane (2006)
Reports on the results of an exploratory empirical study of management practices and cultural characteristics in Barbados, Jamaica and St. Vincent & the Grenadines.